Towards the definition of a nZEB cost spreadsheet as a support tool for the design. (August 2019) - Pernetti, R; Garzia, F; Paoletti, G; Weiss, T
Abstract: The 2010 Energy Performance of Buildings Directive (EPBD recast) [1] established that all new buildings have to reach, by the end of 2020, the nearly-Zero Energy (nZEB) target as set by the Member States. In order to achieve the nZEB standards, while keeping investments sustainable, it is strategic to focus more on the operational phase and to guide the decision-support with a lifetime perspective. In this regard, a crucial step is to adopt a shared methodology for evaluating the Life-Cycle Cost (LCC), in order to minimize the effect of uncertainties, the impact of calculation approach and the variability of the boundaries at EU level. The H2020 CRAVEzero project developed a LCC spreadsheet, aimed at calculating a set of relevant indicators for assessing the cost during the investment phase (design, labour and material costs) as well as during the operational phase of a building (energy and maintenance costs). The LCC spreadsheet implements an approach for normalising the results according to the main relevant boundaries that can affect the comparability at EU level (e.g. energy prices, the national construction costs, the climatic conditions, etc.). Moreover, it introduces a sensitivity analysis that aims to provide the impact that the boundary conditions can have on the results, reducing the uncertainties in the LCC calculations due to a long-term perspective ( http://www.cravezero.eu/lcc spreadsheet/). This paper presents the structure of the LCC calculation approach defined within the project, the structure of the spreadsheet and the main indicators as evaluated for a set of relevant nZEB case studies across Europe.